Os cães de trenó na Terra do Fogo (Argentina) e o que eles têm a nos ensinar sobre o trabalho animal - Fanaro, Luisa Amador (Universidade Federal de São Carlos, 2019)
This dissertation is the result of field research whose objective was to study the relationships between humans (especially mushers and tourists) and sled dogs – which are, from the mushers’ perspective, working dogs – in tourism in Ushuaia (capital of Tierra del Fuego province/Argentina), focusing the ethnography on the practical and semiotic relationships involved in sled rides, dog breeding and the small local sled race, Encuentro Musher. Beyond sled dogs, however, in Tierra del Fuego I came across with several other dogs in other contexts, such as the stray dogs on the streets of Ushuaia and the “wild dogs” – which are a major socioeconomic problem and, therefore, are subject to being eliminated. In this sense, I suggest that in fuegian lands the different statuses of dogs (ranging from domestic/working to wild/feral to interstitial categories) fluctuate according to the existence (or not) of a social “function”, meaning animal work. Thus, I argue that in this context it is only possible to think of sled dogs by reflecting on these other dogs that make up the relationships between humans and animals in this part of the planet. This dissertation’s scope was, then, the elaboration of a multispecific ethnography that took into account both humans and dogs (and sleds), as well as a reflection on animal work, its possibilities and its limits.
Sled dogs in Tierra del Fuego (Argentina) and what they have to teach us about animal work
Los perros de trineo en Tierra del Fuego (Argentina) y lo que nos tienen que enseñar sobre el trabajo animal
Keywords: Humano-animal; Cães; Cães de trenó; Trabalho animal; Human-animal; Dogs; Sled dogs; Animal work; Humano-animal; Perros; Perros de trineo; Trabajo animal; CIENCIAS HUMANAS::ANTROPOLOGIA::TEORIA ANTROPOLOGICA